Hypovitaminosis D in the Middle East and North Africa: Prevalence, risk factors and impact on outcomes - Bassil, Darina (Landes Bioscience, 2013)
Background: The Middle East and North Africa (MENA) region registers some of the highest rates of hypovitaminosis D worldwide.   Aim: We systematically reviewed the prevalence of hypovitaminosis D, rickets and osteomalacia, their predictors and impact on major outcomes, in the region. Methods: Medline, Pubmed and Embase search engines, entering keywords and concepts, combined with individual countries of interest, were used. Search was limited years 2000–2012; and review articles were used for the period preceding year 2000. Results: Rickets and osteomalacia still occur in this sunny region. Hypovitaminosis D prevails, with rates varying 30–90%, considering a desirable serum 25 hydroxy-vitamin D [25(OH)D] of 20 ng/ml. Advancing age, female gender, multi-parity, clothing style, season, socio-economic status and urban living are recognized predictors of hypovitaminosis D in adults. Prolonged breastfeeding without vitamin D supplementation and low dietary calcium intake are the recognized risk factors for rickets and hypovitaminosis D in children.. Associations with pain score and disease activity in rheumatologic disorders, viral load and interleukins in hepatitis C, BMI, lipids and insulin sensitivity, blood pressure, heart failure and mortality are described. Sun exposure in adults decreased prevalence of metabolic syndrome in one study. Few randomized vitamin D trials revealed that the majority of mothers or children failed to achieve a desirable 25(OH)D level, even with doses by far exceeding current recommendations. A trial in adolescent girls reveals substantial bone and lean mass increments. Conclusion: Hypovitaminosis D is prevalent in MENA. The lack of populations based studies, gaps in studies in infants, pre-pubertal children and pregnant women, hinder the development of region specific guidelines and constitute a major obstacle to impact this chronic and most often subclinical disease.